Diospyros kaki and Citrus unshiu Mixture Improves Disorders of Lipid Metabolism in Nonalcoholic Fatty Liver Disease. (24th December 2020) - Shin, Mi-Rae; Shin, Sung Ho; Roh, Seong-Soo
Abstract : Nonalcoholic fatty liver disease (NAFLD) has been a major cause of a chronic liver disease over recent decades and increasing worldwide in parallel with the remarkable growth of obesity. In the present study, we investigate the ameliorative effects of PCM, a combination of Diospyros kaki fruit and Citrus unshiu peel mixture, on high-fat diet- (HFD-) induced NAFLD and clarify the potential mechanisms. PCM in HFD-fed mice was orally administered at a dose of 50 or 100 mg/kg subsequently for 2 months. Thereafter, lipid metabolism parameters and fat synthesis-related genes in the mouse liver were evaluated. Subsequently, body weight changes, liver weight, serum liver function and lipid profiles, and liver pathology were examined, and the relative levels of fatty acid synthesis and β -oxidation gene expression were evaluated by western blot. Serum AST, ALT, and TG levels in the HFD control mice were significantly higher than those of normal mice. Compared with HFD control mice, PCM supplementation increased phosphorylation of AMP-activated protein kinase (AMPK). Peroxisome proliferator-activated receptor (PPAR) α was significantly increased by PCM administration. Continuously, the activation of PPAR α significantly elevated carnitine palmitoyltransferase 1 (CPT-1), a key enzyme in fatty acid β -oxidation, and mitochondrial uncoupling protein 2 (UCP-2), thermogenic regulatory genes, in PCM-treated mice compared with those of HFD control mice. Moreover, PCM inhibits lipogenesis and cholesterol synthesis via suppression of sterol regulatory element binding protein-1 (SREBP-1) and SREBP-2 and its target genes such as acetyl-CoA carboxylase (ACC), fatty acid synthase (FAS), stearoyl-CoA desaturase-1 (SCD-1), and 3-hydroxy-3-methylglutaryl coenzyme A reductase (HMGCR). Taken together, these effects were mediated through activation of AMPK. In the conclusion, PCM improved liver damage in HFD-fed mice and attenuated NAFLD by the activation of PPAR α and the inhibition of SREBPs expression via AMPK-dependent pathways.